SCANning for truth. Scholars’ and practitioners’ perceptions on the use(fulness) of Scientific Content Analysis in detecting deception during police interviews - Goormans, Isabo (Psychology, crime & law, 2024)
SCAN (Scientific Content Analysis) is a verbal credibility assessment (VCA) tool that claims to detect deception in written statements. Although the validity of SCAN is contested in literature, various (law enforcement) agencies across the globe are trained in using SCAN. To date it remains unknown how SCAN is perceived, and to what extent it is used in practice. Based on a scoping review and qualitative survey, we identified practitioners’ and scholars’ perceptions on the use(fulness) of SCAN. Data were collected from 48 participants (35 practitioners and 13 scholars). Key findings illuminate (1) that practitioners apply an incomplete, personalized version of SCAN, (2) that SCAN practitioners are reluctant to abandon SCAN, and (3) that SCAN is considered incompatible with (Belgian) legislation on police questioning. Based on practitioners’ expressed needs and concerns, we present several alternatives for SCAN, as well as recommendations on how a shift to other techniques can be facilitated.